Webster's New Word Thesaurus - Laird, Charlton (New Yor, U.S.A. : Pocket Books, 2003)
This edition of Webster's New World Thesaurus derives ultimately from Charlton Laird's original thesaurus, which was first published in 1948 under the title Laird's Promptory. The entry arrangement and editorial principles of the original are still much in evidence in the present edition. The work draws heavily on the successful innnovations of its predecessors and offers new contributions drawn from the evolvin database of new words in American English recorded by the staff of Webster's New World College Dictionary, fourth edition
WEBSTER'S NEW WORLD THESAURUS STAFF FOREWORD GUITE TO THE USE OF THIS BOOK I. ARRANGEMENT OF ENTRIES II. PART-O-SPEECH LABELS III. THE ENTRY BLOCK IV. SUGGESTIONS FOR USING THE THESAURUS V. ABBREVIATIONS AND SYMBOLS USED IN THIS BOOK
Incluye contents, foreword, guide to the use.
Keywords: THESAURUS; ENCICLOPEDIAS Y DICCIONARIOS; DICCIONARIO - SINÓNIMOS Y ANTÓNIMOS